ASSOCIATION OF RISK FACTORS FOR NON-COMMUNICABLE DISEASES WITH HEALTH CARE RESOURCES UTILIZATION AND TEMPORARY DISABILITY ACCORDING TO DATA OF POPULATION STUDY IN RUSSIAN FEDERATION - E. I. Suvorova; S. A. Shalnova; A. V. Kontsevaya; A. D. Deev; A. V. Kapustina; Yu. A. Balanova (Рациональная фармакотерапия в кардиологии)
Aim. To analyze the associations of health care system resources utilization and temporary disability (TD) with the main risk factors (RF) for cardiovascular diseases (CVD) in working age population based on ESSE-RF study data.Material and methods. The analysis was based on ESSE-RF study data (13 regions of the Russian Federation). Standard epidemiological survey methods and evaluation criteria were used. The analysis included results of a survey of the ESSE-RF study participants about the utilization of health services and TD during last 12 months. Average number of outpatient visits, hospitalizations (including duration of in-hospital treatment and number of cases), ambulance calls and TD (a number of days and cases) per one study participant and associations with RF for CVD were estimated. We conducted a comparative analysis of the utilization of health services and TD in association with cardiovascular RF, also logistic regression analysis was performed to predicting the likelihood of outpatient visits, hospitalizations, ambulance calls and TD.Results. A total of 21,923 individuals in the 25-64 age group were included: men – 8,373 (38%) and women – 13,550 (62%). Number of men who was hospitalized significantly increased in group with tobacco consumption (1,41; p<0,05) and obesity (1,32; p<0,05), also number of participants who call to ambulance increased among smoking men (1,41; p<0,05) and with hyperglycemia (1,38; p<0,05), at the same time number of persons with cases of TD significantly increased just only among smokers (1,29; p<0,05). At the same time, number of women who used health services (exclude in-hospital treatment) and who had a case of TD was significantly increased just only among smokers. The frequency of the utilization of health services and TD cases, the average number of days of hospitalizations and days of TD cases for 1 person depending on the presence/absence of RF had small difference in both men and women. Female obesity is the most resource-intensive RF, as well as male smoking, and was associated with an increase in the likelihood of using all types of medical care and TD cases. Smoking and hyperglycemia significantly increased the likelihood of utilization the most of health services in women, whereas in men hyperglycemia increased only the probability of ambulance calls (1,38; p<0,05), and obesity – only hospitalizations (1,32; p<0,05). Hypertension significantly affected only to ambulance calls in both men and women. Hypercholesterolemia was associated with decreased likelihood of the utilization health services in men.Conclusion. So, there is a significant association of the health care utilization with the RF depending on the type of medical care, sex and RF.